Effects of Low Temperature Stress on Source–Sink Organs in Wheat and Phosphorus Mitigation Strategies - Xu, Hui; Hassan, Muhammad A.; Sun, Dongyue; Wu, Zhaochen; Jiang, Gang; Liu, Binbin; Ni, Qianqian; Yang, Wenkang; Fang, Hao; Li, Jincai; Chen, Xiang (Frontiers in Plant Science, 2022)
ABSTRACT In the 21st century, mankind is facing many challenges, including unexpected climate change, booming world population, and serious concerns over global food security. Wheat is a leading cereal crop that largely fulfils the global food demands. Low temperature stress accompanied by nutrient starved soils drastically influences wheat’s source-sink relationship that leads to poor quality and lower grain yield. This review paper mainly discussed how low temperature cyto-physiologically damages the source-sink organs (leaf, root and spike) of wheat, and how phosphorus application alleviates these negative effects. We aimed to establish a solid foundation for improving the low temperature stress tolerance and efficient utilization of phosphorus in wheat. We proposed strategies to enhance wheat's adaptive capacity besides mitigating the risks of cold anticipated with climate change, and rational suggestions based on integrated management approaches that are associated with agronomic and breeding perspectives. Keywords: integrated management approach, low temperature stress, phosphorus, regulation mechanism, Triticum aestivum L.